Pathophysiological Role of Genetic Factors Associated With Gestational Diabetes Mellitus - Ortega-Contreras, B.; Armella, A.; Appel, J.; Mennickent, D.; Araya, J.; González, M.; Castro, E.; Obregón, A. M.; Lamperti, L.; Gutiérrez, J.; Guzmán-Gutiérrez, E. (Frontiers in Physiology, 2022)
Gestational Diabetes Mellitus (GDM) is a highly prevalent maternal pathology characterized by maternal glucose intolerance during pregnancy and associated to severe complications for both mother and offspring. Several risk factors have been associated to GDM; among them genetic predisposition is one of the most important. Numerous single nucleotide polymorphisms (SNPs) in genes that act at different levels on various tissues could generate changes in expression levels and activity in proteins that result in a dysfunction in glucose and insulin metabolism. In this review we describe various SNPs; which, according to the literature increase the risk of developing GDM. These SNPs include: (1) those associated with transcription factors that regulate insulin production and excretion, such as rs7903146 (TCF7L2) and rs5015480 (HHEX); (2) others that cause a decrease in protective hormones against insulin resistance such as rs2241766 (ADIPOQ) and rs6257 (SHBG); (3) SNPs that cause modifications in membrane proteins, generating a dysfunction in insulin signaling or cell transport in the case of rs5443 (GNB3) and rs2237892 (KCNQ1); (4) those associated with enzymes such as rs225014 (DIO2) and rs9939609 (FTO) which cause an impaired metabolism, resulting in an insulin resistance state and other polymorphisms (5) some which are associated with growth factors such as rs2146323 (VEGFA) and rs755622 (MIF) which could cause changes in expression levels of these proteins producing endothelial dysfunction and increase of pro-inflammatory cytokines, characteristic of GDM. While the pathophysiological mechanism is unclear, this review describes various approaches to the effects of these polymorphisms on the predisposition to develop GDM.